Proceedings of the 5th Annual International Conference on Accounting Research (AICAR 2018) 2019
DOI: 10.2991/aicar-18.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee: Woman, Experience, Education on Earnings Management

Abstract: The purpose of this research is to obtain empirical evidence about the effect of board size, board independence, directors expertise, board meetings, audit committee expertise, audit committee meetings, audit committee woman, audit committee education, concentrated shareholders, and managerial ownership on earnings management. The population in this research is all listed manufacturing companies in Indonesia Stock Exchange during 2013 to 2016. Samples are obtained through purposive sampling method, in which 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
3
5
0
2
Order By: Relevance
“…Kumaat (2013) and Lawal, Nwanji, Opeyemi, and Adama (2018) found that independent commissioners have a negative effect on earnings management. Similar research was produced by research conducted by Kapoor andGoel (2017), andFlorencea andSusanto (2018) found that the size of the board of commissioners does not affect earnings management. Kumaat (2013) found that independent commissioners positively affect earnings management, and the audit committee does not affect earnings management.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Kumaat (2013) and Lawal, Nwanji, Opeyemi, and Adama (2018) found that independent commissioners have a negative effect on earnings management. Similar research was produced by research conducted by Kapoor andGoel (2017), andFlorencea andSusanto (2018) found that the size of the board of commissioners does not affect earnings management. Kumaat (2013) found that independent commissioners positively affect earnings management, and the audit committee does not affect earnings management.…”
Section: Introductionsupporting
confidence: 55%
“…Women's qualities on audit committees have the potential to worsen profit management. The result is supported by research conducted by Thiruvadi and Huang (2011), Qi and Tian (2012), Salleh, Hashim, Mohamad (2012), Susanto (2016), and Florencea and Susanto (2018). Research conducted by Loualalen, Khemakhem, and Fontaine (2015) and Abdullah and Ismail (2016) found that gender on the audit committee did not affect profit management.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The characteristics of women on the audit committee can reduce earnings management. This is supported by research conducted by Thiruvadi & Huang (2011), Qi & Tian (2012), Salleh et al (2012), Susanto (2016), and Florencea & Susanto (2019). The opposite was obtained from research conducted by Loualalen et al (2015), and Abdullah & Ismail (2016) found that gender on the audit committee had no effect on earnings management.…”
Section: Introductionmentioning
confidence: 84%
“…This is supported by research conducted by Zalata et al (2018), Salleh et al (2012), Thiruvadi & Huang (2011), who found that women's audit committees can reduce earnings management. Florencea & Susanto (2019) and Susanto (2016) also found that women's audit committees can reduce earnings management in manufacturing firms in Indonesia. H 3 : More female presence on the audit committee has a negative effect on earnings management…”
Section: Female In the Audit Committee And Earnings Managementmentioning
confidence: 97%